Three-dimensional scaffold platform for controlled therapeutic drug and non-viral gene delivery to enhance nerve regeneration and remyelination in spinal cord injuries - Nguyen, Lan Huong (2018)
Spinal cord injuries (SCI) are followed by a complex series of events that contribute to the failure of regeneration. To date, there is no repeatable treatment that can restore the injury-induced loss of function. Since damaged spinal axons do not regenerate in their native inhibitory microenvironment, a combined application of biomaterials and neurotrophic factors that induce nerve regeneration emerges as an attractive treatment for SCI. Moreover, damage of myelin membranes, that ensheath axons, and failure of remyelination after nerve injury can disrupt neural signals, leading to nerve degeneration. In this study, a scaffold-mediated RNA interference approach using nanofiber scaffolds incorporated with microRNAs (miRs) is proposed to direct and enhance nerve regeneration and remyelination after SCI. We report the novel use of sparsely distributed aligned nanofibers to provide contact guidance for regrowth of axons in vivo. The scaffold comprises of aligned poly (ε-caprolactone-co-ethyl ethylene phosphate) (PCLEEP) nanofibers that are supported within a collagen hydrogel. To demonstrate the efficacy of our PCLEEP-collagen hybrid scaffold in achieving effective local drug/gene delivery in vivo, we incorporated neurotrophin-3 (NT-3) as the model protein and miR-222 as the model miR. The scaffolds were implanted into a hemi-incision injury, which was created at level C5 in the rat spinal cord. The results showed that our biofunctionalized scaffolding platform effectively provided bio-mimicking contact guidance and allowed the controlled delivery of various drugs and therapeutic biomolecules of drastically different nature and molecular weights. After 3 months of implantation, the results showed that the nanofiber scaffold elicited the longest attainable neurite length of 1039.53 ± 264.99 μm, which was significantly longer as compared to the untreated group (371.78 ± 194.83 μm, p ≤ 0.01) and the isotropic hydrogel-treated group (287.42 ± 100.11 μm, p ≤ 0.001). Importantly, the regenerated axons and blood vessels formed along the direction of the aligned nanofibers, regardless of their orientation. Moreover, the presence of the nanofiber scaffolds did not affect tissue scarring and inflammatory reaction. Taken together, these findings demonstrate that our aligned nanofibers-hydrogel scaffold is a promising bio-functional platform for nerve injury treatment. On the other hand, promoting remyelination after SCI is challenging since oligodendrocyte precursor cells (OPCs) often fail to differentiate and mature into oligodendrocytes (OLs), the myelin-forming cells of the CNS. We have previously demonstrated that miR-219 and miR-338 (miR-219/miR-338), when coupled with fiber topography, enhanced OPC differentiation and maturation in vitro. Therefore, our vision for future study is to incorporate miR-219/miR-338 into our scaffold platform to promote OPC maturation and differentiation, hence enhancing remyelination for SCI treatment. However, SCI is a complicated process that involves a vast number of cell types beside OPCs such as microglia and astrocytes. Non-specific uptake of miR-219/miR-338 by these cells may cause undesired side effects that potentially interfere with the regeneration process of the nervous system. Therefore, we also examined the effect of miR-219/miR-338 on microglia and astrocytes in vitro. In addition, we studied the influence of astrocytes on OPC maturation and differentiation under the presence of these miRs in the injury mimicking condition in vitro.